التجربة الديمقراطية الجزائرية والموقف السوفيتي منها 1988-1992 - الجبوري، عاصم حاكم عباس; أمانة، نضال أبو جواد (جامعة بابل - مركز بابل للدراسات الحضارية والتاريخية, 2018)
أدت طبيعة الأحداث السياسية في عام ١٩٨٥، إلى إحداث تبدلات معمقة في إدراك الواقع العام الذي تعيشه تلكم البلدان، التي بدت أنها تحيي اختبار مستجد فرضتها عليها الحتمية التاريخية فأخذت تتناول حلول له، وعمدت إلى الفلسفة لعلها تجد فيها فكره وتنظير جديد، بعد بلوغ غورباتشوف هرم السلطة في الاتحاد السوفيتي. أسهمت التبدلات السياسية التي شهدها الاتحاد السوفيتي ١٩٨٥-1991 في تحرر أوربا الشرقية، وتثبيت رئاسة الولايات المتحدة الأمريكية للعالم، وأيضا خلخلت التغيرات السوفيتية سلطة الأنظمة السياسية التي تسير في فلكها، وحفزت الباحثين والمهتمين بالشأن السوفيتي، إلى دراستها وتحري عن أسباب تشكلها ومنها التجربة الديمقراطية الجزائرية، والتي تكمن في خطورة انعكاساتها على العديد من بلدان العالم وبخصوص المنطقة العربية. إن مسألة التبصر ضروري لتناول إشكالات التجربة الديمقراطية الجزائرية ضمن مبدأ غياب الداعم الخارج، إذ شغلت المسألة الجزائرية حيز مهم من المناقشات بخصوصها، والموقف الدولي منها وخاصة الموقف السوفيتي والتدخلات الأجنبية. قسم البحث على مقدمة وثلاث محاور وخاتمة، درس المحور الأول: متغيرات الفعل السياسي وإقرار الديمقراطية في الجزائر، بينما تطرق المحور الثاني: الانتخابات الجزائرية ومحاولات تطبيق الديمقراطية، وبين المحور الثالث: أثر غياب الاتحاد السوفيتي في الموقف الدولي للأزمة الجزائرية.
The nature of the political events in 1985 led to profound changes in the perception of the general reality of these countries, which seemed to revive a new test imposed by historical determinism and took solutions to it, and I went to philosophy to find a new idea and perspective, after the arrival of Gorbachev pyramid Power in the Soviet Union. The political changes witnessed by the Soviet Union in 1985-91 contributed to the liberation of Eastern Europe and the consolidation of the presidency of the United States of America to the world. The Soviet changes also undermined the authority of the political regimes in its orbit and motivated researchers and interested in the Soviet affairs to study them and investigate their causes, Which lies in the seriousness of its repercussions on many countries of the world and the Arab region. The issue of foresight is necessary to deal with the problems of the Algerian democratic experiment within the principle of the absence of outside support. The Algerian question has occupied an important space of discussions regarding it, the international position, especially the Soviet position and foreign interventions. The first section deals with the variables of political action and the establishment of democracy in Algeria, while the second axis dealt with the Algerian elections and the attempts to apply democracy, and the third axis: the absence of the Soviet Union in the position.
Keywords: الديمقراطية; الانتخابات الجزائرية; الاتحاد السوفيتى; الديمقراطية فى الجزائر; الأزمة الجزائرية